Does the human capital of board directors add value to firms? Evidence from an Asian market - Nguyễn, Văn Tuấn (Taylor & Francis, 2022)
This paper investigates the effect of the human capital of directors on the financial performance of Vietnamese-listed companies. The dynamic system generalised method of moments (system GMM) estimator is used to examine a panel data-set consisting of 315 firm-year observations over a four-year period from 2008 to 2011. In line with resource dependence theory, we report that the human capital of directors appears to have a positive influence upon a firm’s financial performance. To the best of our knowledge, this study is the first work on the topic of human capital of directors and firm performance for publicly listed companies in Vietnam. This study, by applying a dynamic longitudinal modelling approach, extends the nascent literature on board human capital as well as more generally to the corporate governance literature by providing robust empirical evidence showing that the general human capital of board directors may add value to firms. Our finding, therefore, supports the efforts made by Vietnamese policy-makers in setting up qualification standards as well as skills diversity for the boards.